A history of control engineering, 1800-1930 - Bennett, S. (Stuart) (London, United Kingdom Institution of Engineering and Technology, 1979)
Dr. Bennett traces the growing awareness of the importance and the significance of the concept of feedback in engineering and treats in detail the technical developments that contributed to this awareness. There follows an account of the development of steam and hydraulic servomechanisms and their application to the control of ships and aircraft.
Electronic reproduction.
Keywords: Automatic control -- History; Electronic books